Optimal Timing for Expanding Diagnostic Laboratories, South Korea - Jae-Sun Park; Gab Jung Kim; Sang Won Lee (Emerging Infectious Diseases)
The rapid expansion of testing capacity is imperative for an adequate response to infectious diseases, such as COVID-19. South Korea rapidly secured large-scale testing during the early stages of COVID-19 in 2020 by leveraging the country’s experience with the 2015 Middle East respiratory syndrome outbreak; the initial response was relatively successful. A key difference between the 2 outbreak responses was the expansion from public to private testing laboratories during the COVID-19 pandemic. Expanding testing capacity during an infectious disease crisis should involve consideration of the overall response system and social conditions and not just the number of patients. If there are concerns about a crisis developing, testing capacity expansion should begin as soon as possible. Furthermore, accuracy should be ensured, especially when testing capacity is expanded. South Korea’s experience in developing diagnostic systems and adopting testing strategies underscores the value of proactive and well-timed preparedness for emerging infection disease outbreaks.